2011
DOI: 10.1080/14724049.2011.555554
|View full text |Cite
|
Sign up to set email alerts
|

The third criterion of ecotourism: are ecotourists more concerned about sustainability than other tourists?

Abstract: The third criterion of ecotourism: Are ecotourists more concerned about sustainability than other tourists?Ecotourism can be defined by three core criteria: nature, learning and sustainability. The ecotourist market has been segmented by the nature and learning criteria only. It has been assumed that ecotourists are environmentally concerned and therefore sustainability is a factor in their decisionmaking. However, little empirical research has confirmed this assumption. This study surveyed 243 respondents par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 25 publications
(46 reference statements)
3
29
1
5
Order By: Relevance
“…The results indicated that EnJ is the most important motivational factor, which differs from previous studies on the motives of other nature-based tourists, in which knowledge seeking was found to be the most important motive (Beaumont 2011;Eagles 1992;Luo and Deng 2008). As a subset of nature-based tourists, geotourists may exhibit different travel motivations in that they may be more influenced by the socio-psychological motivation to admire and enjoy the geopark than by intellectual curiosity about geological knowledge (Hurtado et al 2013).…”
Section: Discussioncontrasting
confidence: 77%
“…The results indicated that EnJ is the most important motivational factor, which differs from previous studies on the motives of other nature-based tourists, in which knowledge seeking was found to be the most important motive (Beaumont 2011;Eagles 1992;Luo and Deng 2008). As a subset of nature-based tourists, geotourists may exhibit different travel motivations in that they may be more influenced by the socio-psychological motivation to admire and enjoy the geopark than by intellectual curiosity about geological knowledge (Hurtado et al 2013).…”
Section: Discussioncontrasting
confidence: 77%
“…First, it is essential to acknowledge that ecotourism is a much-debated type of tourism in theory and in practice and efforts to pin it down are many (Beaumont, 2011;Buckley, 2013;Donohoe & Needham, 2006;Fennell, 2001Fennell, , 2002Wearing & Neil, 2009;Weaver, 2005). Ecotourism's practice is diverse and expressed in many different ways and can fall under the functioning of an ecolodge within or adjacent to a natural area, it can be a bus tour through a national park and/or it may comprise guided walks and/or independent visits to see natural attractions such as landscapes, wild flowers, particular landforms and animal life.…”
Section: Introductionmentioning
confidence: 99%
“…As a response to and reflection of the damage mass tourism brings to the ecological environment, sustainable tourism has aroused the attention of all tourism stakeholders. According to Beaumont, tourists with eco-awareness tend to become the major tourism market because this type of tourist travels more frequently than others [3]. Therefore, sustainable tourism has taken an increasingly prominent position in the entire market [4].…”
Section: Introductionmentioning
confidence: 99%